Myśl ekonomiczna kalwinizmu - Chmielewska, Justyna (Annales. Etyka w Życiu Gospodarczym, 2023)
The aim of the paper is to present the economic thoughts of John Calvin and hisfollowers, referring to current issues, such as money lending, usury, or work. Thelatter, according to the famous thesis of Max Weber, received spiritual value byacting as a bridge between God's will and daily life. The hypothesis of this articlediffers somewhat from this conviction, assuming that the main economic elementsof Calvinist thought have been the consequence of the release of temporal realitiesfrom the influence of the direct action of God, according to the protestant theologyof the radical separation of nature and grace. Initiated by Protestantism, the dichotomyof nature and grace seems to have important consequences for economicthought. The salvific dimension of human fate remained in the hands of God, hedepends entirely on its favour in connection with the dogma of predestination. Inthe earthly life, a human being was treated as a part of nature, his survival dependedon skill and determination. in the struggle with nature, devoid of the grace ofGod, ruled by the law of necessity. Survival and a better life depended primarilyon human labour and effort. The flourishing of economic life has resulted not onlyfrom the ethical role of work, but also from the fact that it was no longer inhibitedby religious restrictions. Thus, modern man was born, more and more aware of hissubjectivity, subordinating nature to himself building the human world in place ofthe natural world. Building a modern society and economy is part of the Protestantethos of mastering nature.